Health outcomes following COVID-19 infection and vaccination in hereditary hemorrhagic telangiectasia - Christopher M. Tarulli; Xiayi Ma; Kamalprit Chokar; Nicholas T. Vozoris; Marianne S. Clancy; Marie E. Faughnan (Orphanet Journal of Rare Diseases)
Abstract Background There has been concern that individuals living with Hereditary Hemorrhagic Telangiectasia (HHT) could be at higher risk for poor outcomes if infected with SARS-CoV2, the virus that causes COVID-19 disease. As literature is lacking on outcomes on COVID-19 infection and vaccination in HHT, the objectives of this study were to determine and assess outcomes in HHT, as well as quantify vaccination rates and vaccination side effects in a large cohort of individuals with HHT. Method Individuals previously recruited to OUR HHT Registry at St. Michael’s Hospital, Toronto were contacted for participation in this study. Data were collected during annual assessment through a series of questionnaires asking specifically about HHT complications, treatments, and symptom management, along with COVID infection and vaccination data. Results We attempted to contact all 262 subjects recruited to the registry. Of these, 215 (82.1%) responded at least once regarding COVID-19 related inquiries between April 2020 and August 2022, and these individuals formed our study sample. Forty-nine COVID-19 infections were reported in 47/215 (21.9%) individuals. Among 47 patients with recorded COVID-19 infection, 2/47 (4.3%) required urgent care and 7/47 (14.9%) were hospitalized following infection. Of the 7 individuals who were hospitalized, 3 (42.9%) required new supplemental oxygen. Zero deaths were reported due to COVID-19 infection. COVID vaccination history was available in 147/215 (68.4%). Of these, 135/147 (91.8%) of individuals reported vaccination and side effects were mild. Discussion While our sample population is much like the general HHT population with regards to gender, HHT symptoms, and genetics, study limitations including survivor bias, lack of vaccine effectiveness assessment, and participant reported data should be acknowledged. Conclusion Our results suggest that HHT patients are not at higher risk of severe infection with COVID-19 compared to the general population. Vaccination rates are high with only mild side effects being observed.